KARAKTERISTIK SIFAT MEKANIS ANTARA TIGA PRODUK MANUFAKTUR ELEKTRODA E6013 - Basori Basori; Ferry Budhi Susetyo (Universitas 17 Agustus 1945 Jakarta, 2018)
The type of electrode used in the SMAW process has many types, such as E 6010, E 6011, E 6012, E 6013, E 6020, E6027. In this case the type E 6013 is the most widely used. Certainly the type E 6013 is produced by different manufacturers as well. From penelurusan researchers of this type have different prices in accordance with companies that sell it. For that reason researchers are interested to compare the three manufacturing outputs for the type E 6013 in terms of its mechanical properties. Making a specimen welding electrode cut material to be used. then sandpaper the material that has been cut so that no remaining pieces are still attached. The next step to do the welding process with three types of E6013 elekroda. The welding is carried out until it reaches the layer layer 10 mm thickness, then the bottom plate is discarded and the weld deposit deposits only The impact strength and surface hardness value are inversely proportional. For the impact test, the E1 electrode sample specimen has the highest impact strength value and the E3 electrode sample specimen has the lowest impact strength value. While on the hardness test specimen E3 electrode sample has the highest hardness value and sample specimen E1 electrode has the lowest hardness value. This can prove that the harder the object is the more brittle the object.